Integrating nTMS Data into a Radiology Picture Archiving System. - Mäkelä, Teemu; Vitikainen, Anne-Mari; Laakso, Aki; Mäkelä, Jyrki (Journal of Digital Imaging, 2015)
Navigated transcranial magnetic stimulation (nTMS) is employed in eloquent brain area localization prior to intraoperative direct cortical electrical stimulations and neurosurgery. No commercial archiving or file transfer protocol existed for these studies. The aim of our project was to establish a standardized protocol for the transfer of nTMS results and medical assessments to the end users in pursuance of improving data security and facilitating presurgical planning. The existing infrastructure of the hospital's Radiology Department was used. Hospital information systems and networks were configured to allow communications and archiving of the study results, and in-house software was written for file manipulations and transfers. Graphical user interface with description suggestions and user-defined text legends enabled an easy and straightforward workflow for annotations and archiving of the results. The software and configurations were implemented and have been applied in studies of ten patients. The creation of the study protocol required the involvement of various professionals and interdepartmental cooperation. The introduction of the protocol has ended previously recurrent involvement of staff in the file transfer phase and improved cost-effectiveness.